MODERN APPROACHES TO THE ADDITIONAL FOOD ADMINISTRATION IN INFANTS - E.A. Pyr’yeva (Вопросы современной педиатрии)
Author gives an account of main principles of additional food organization in infants. New data on the influence of additional food on the growth, health and development of infant and child are presented. Special attention is given to the individual approach to the administration of additional food taking into account health and level of development of child. The tactics of additional food introduction to children with alimentary-dependent pathology (alimentary allergy, delay of physical development, iron-deficient anemia) is given. Author shows importance of industrially produced additional food in prophylactics of deficient states, particularly, deficiency of iron and zinc.Key words: children, additional food, alimentary allergy, delay of physical development, anemia.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(2):150-155)